EGFR inhibition augments the therapeutic efficacy of the NAT10 inhibitor Remodelin in Colorectal cancer - Yongbin Zheng; Dan Song; Ming Guo; Chenhong Wang; Mingzhen Ma; Gongcai Tao; Licui Liu; Xiaobo He; Fengyu Cao; Dan Luo; Qingchuan Zhao; Zhongyuan Xia; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Colorectal cancer (CRC) is the second leading cause of cancer-related death worldwide, and treatment options for advanced CRC are limited. The regulatory mechanisms of aberrant NAT10-mediated N4-acetylcytidine (ac4C) modifications in cancer progression remains poorly understood. Consequently, an integrated transcriptomic analysis is necessary to fully elucidate the role of NAT10-mediated ac4C modifications in CRC progression. Methods NAT10 expression levels were analyzed in CRC samples and compared with those in corresponding normal tissues. The potential mechanisms of NAT10 in CRC were investigated using RNA sequencing, RNA immunoprecipitation sequencing, and acetylated RNA immunoprecipitation sequencing. Additional in vivo and in vitro experiments, including CCK-8 assays, colony formation and mouse xenograft models, were conducted to explore the biological role of NAT10-mediated ac4C modifications. We also evaluated and optimized a potential treatment strategy targeting NAT10. Results We found that NAT10 is highly expressed in CRC samples and plays a pro-oncogenic role. NAT10 knockdown led to PI3K-AKT pathway inactivation, thereby inhibiting CRC progression. However, treatment with the NAT10 inhibitor Remodelin induced only a limited and reversible growth arrest in CRC cells. Further epigenetic and transcriptomic analysis revealed that NAT10 enhances the stability of ERRFI1 mRNA by binding to its coding sequence region in an ac4C-dependent manner. NAT10 knockdown decreased ERRFI1 expression, which subsequently activated the EGFR pathway and counteracted the inhibitory effects on CRC. Based on these findings, we demonstrated that dual inhibition of NAT10 and EGFR using Remodelin and the EGFR-specific monoclonal antibody cetuximab resulted in improved therapeutic efficacy compared to either drug alone. Moreover, we observed that 5-Fluorouracil promoted the interaction between NAT10 and UBR5, which increased the ubiquitin-mediated degradation of NAT10, leading to ERRFI1 downregulation and EGFR reactivation. Triple therapy with Remodelin, cetuximab, and 5-Fluorouracil enhanced tumor regression in xenograft mouse models of CRC with wild-type KRAS, NRAS and BRAF. Conclusions Our study elucidated the mechanism underlying 5-Fu-induced NAT10 downregulation, revealing that NAT10 inhibition destabilizes ERRFI1 mRNA through ac4C modifications, subsequently resulting in EGFR reactivation. A triple therapy regimen of Remodelin, cetuximab, and 5-Fu showed potential as a treatment strategy for CRC with wild-type KRAS, NRAS and BRAF.